POSTKOMODIFIKASI PORTAL BERITA DI KOMPAS.COM PADA PEMBERITAAN VAKSIN COVID-19 - Bayquni Bayquni; Prasetya Yoga Santoso (Universitas Prof. Dr. Moestopo (Beragama), 2021)
The Indonesian government has issued a government policy to overcome the transmission of Covid 19 in the country. Massive media reports, one of which is Kompas.com. The coverage of the Covid-19 vaccine on Kompas.com for the period August - September 2020 is the object of this research. The purpose of this study is to analyze, and reveal how the political discourse in the news of the Covid 19 Vaccine and how the post-commodification of information occurs through the news of the Covid 19 vaccine on Kompas.com. This research is an interpretive qualitative research with a critical paradigm with Norman Fairclough's Critical Discourse Analysis. Discourse analysis in this theory is carried out at three levels, namely text, discursive practice, and sociocultural practice. The results of the study show that the political discourse that has developed in the news of the Covid 19 vaccine on Kompas.com is the practice of media commodification. Political discourse in reporting the Covid-19 vaccine is represented as an identity battle between related parties, especially in government circles. The news on the Covid 19 vaccine, narrated by Kompas.com, is very political to gain recognition, support, and representation of media ideology by turning news into a millennial industry, ammunition for political competition and political partisan identity within the government.